Tasawuf Jawa: Kajian Filologis terhadap Naskah Suluk Ahya Ngulumodin - Safi’i, Muhammad (Universitas Tidar, 2025)
This research aims to describe the condition of Suluk Akya Ngulumodin manuscripts including: This research aims to describe the condition of the manuscript including: manuscript inventory, manuscript description and text study. The edited text uses a standard or critical edition accompanied by critical tools, and the translation of the text uses the following methods: literal, content, and free; Philological theory is used to reveal the cultural results contained in the manuscript. The object of this research is manuscript NB. 1768 of the National Library of Indonesia and BLK.0423-IS44 of the University of Indonesia Library. The results of this research are in the form of edits. Editing Suluk Akya Ngulumodin means preparing the manuscript ready to be published or printed. Editing in philology is the provision of a manuscript that is close to the original, which is a good and correct manuscript. Good means that it is easy to read and understand because it has been transcribed or transliterated (from Javanese script to Latin script) and the spelling has been adjusted to the target language. Correct means that it can be accounted for the validity of its text content, because it has been cleaned of writing errors through in-depth research.